PERAN SISTEM INFORMASI MANAJEMEN PENDIDIKAN DALAM MENDUKUNG PENGAMBILAN KEPUTUSAN STRATEGIS UNTUK PENINGKATAN KINERJA LEMBAGA - Rizky Ardian Khoirul Putera; Reza Stefiona Laxsniky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of the Education Management Information System in supporting strategic decision-making to improve the performance of educational institutions. The challenges of managing educational institutions in the 21st century require data-driven managerial transformation that is both accurate and efficient. The Education Management Information System is presented as an integrative solution in supporting this process. The research method used is Library Research with data collection techniques through literature review from various relevant sources, while data analysis uses the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the Education Management Information System acts as the foundation for data-driven decision making by integrating data from all work units and presenting it in the form of real-time strategic information. The use of this system has a significant impact on improving institutional performance through increased effectiveness in achieving strategic objectives, operational efficiency, and public accountability. However, its implementation faces challenges in the form of resistance to change and data quality issues. Therefore, its successful implementation requires strong commitment from leaders and the instilling of a data-based mindset in the entire academic community.